Activation and Termination Detection on Distributed Systems - Baraldi, Waldemar (2004)
Facing the different approaches to process activation and global termination detection on distributed systems, this paper performs a practical comparison between the mainly opposed centralized and distributed models. Firstly, they were implemented to solve both the activation and termination detection problems. Based on processing performance and communication overhead metrics, both systems were evaluated running on various parametrized environments. As a result, we present the values obtained and the final conclusions. The overall design was made following an object oriented methodology, which was coded using C++. The inter-process communication was carried out using the PVM libraries.